2012
DOI: 10.3109/0886022x.2012.718950
|View full text |Cite
|
Sign up to set email alerts
|

Concomitance of Gitelman Syndrome and Familial Mediterranean Fever: A Rare Case Presentation

Abstract: We report a case that has Gitelman syndrome (GS) and familial Mediterranean fever (FMF) presenting with recurrent arthritis of right knee and heel pain. Investigations showed hypokalemia and hypomagnesemia with urinary magnesium wasting. Genetic analysis revealed the presence of heterozygous E148Q mutation in the MEFV gene. Management with potassium, magnesium supplements, spironolactone for GS, and colchicine for FMF resulted in a signicant improvement in symptoms. To the best of our knowledge, this is the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Other rarer associations have been reported, with: systemic lupus erythematosus [46][47][48], sarcoidosis [38], Blau syndrome [49], Kartagener syndrome [50], Gitelman syndrome [51], Fabry syndrome [52], celiac disease [53], polymyositis [54], juvenile dermatomyositis [55], beta-thalassemia [56], atrophic polychondritis [57], fibromyalgia [58], eosinophilic gastroenteritis [59], and tumor necrosis factor receptor-1 syndrome (TRAPS syndrome) [60].…”
Section: Familial Mediterranean Fever and Its Rarer Associationsmentioning
confidence: 99%
“…Other rarer associations have been reported, with: systemic lupus erythematosus [46][47][48], sarcoidosis [38], Blau syndrome [49], Kartagener syndrome [50], Gitelman syndrome [51], Fabry syndrome [52], celiac disease [53], polymyositis [54], juvenile dermatomyositis [55], beta-thalassemia [56], atrophic polychondritis [57], fibromyalgia [58], eosinophilic gastroenteritis [59], and tumor necrosis factor receptor-1 syndrome (TRAPS syndrome) [60].…”
Section: Familial Mediterranean Fever and Its Rarer Associationsmentioning
confidence: 99%
“…Improvement of biochemical abnormalities with potassium and magnesium supplementations resulted in clinical improvement at the end of the follow-up of two years in their patient. 4 Our patient had clinical and laboratory features of FMF and GS, also homozygous mutations in both M694V and SLC12A3 genes. The clinical symptoms such as polyuria and polydipsia, and biochemical findings of GS in our patient improved with oral potassium and magnesium supplementations in 20 months of follow-up period.…”
Section: Discussionmentioning
confidence: 59%
“…Coexistence of GS and FMF has not yet been reported in childhood. [11][12][13] Erten et al 4 reported the coexistence of GS and FMF in a 46-year-old man with heterozygosity for E148Q mutation in MEFV without a confirmed mutation in SLC12A3. This patient was diagnosed with GS based on clinical and biochemical findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation